KEMISKINAN DI SRIHARJO DEWASA INI - Indroyono, Puthut; Junarsin, Eddy (Journal of Indonesian Economy and Business, 2002)
Economic improvements should be appraised from growth, ethical, and sustainable development point of views. Hence, economic growth is only one of the improvement criteria. Subsequently, institutional economics hypothesizes that the roles of institutions and cultures are obvious in designing economic system and policies in a particular country. In other words, not one economic system is appropriate for every country. Accordingly, in order to find out that people economy is the most suitable economic system in Indonesia, we visited the village of Sriharjo on November 28, 2001. The results show that albeit its use of traditional economic system (agriculture) and financial institution, Sriharjo survived when the monetary crisis hit the village economy. This empirical result supports the hypothesis of institutional economics that cultures can help establish a strong foundation in an economy. The conclusion is in line with previous research finding by Mubyarto, Masri Singarimbun, and David Penny.Keywords: Institutional economics, people economy.